2004
DOI: 10.1023/b:mcbi.0000049365.60694.81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some volatile oils on the affinity of intact and oxidized low-density lipoproteins for adrenal cell surface receptors

Abstract: Extensive research has shown that a high plasma concentration and oxidation of low-density lipoproteins (LDL) has an important role in atherogenesis. The affinity of LDL to its classic receptor is reduced due to oxidation. Instead, it is taken up by scavenger molecules in macrophages, as a result of which foam cells are formed that have a major role in increasing the subendothelial fat layers of the blood vessels. In the present study the antioxidant effect of eight volatile compounds in plant essences, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…This inhibition is due to a retarded oxidation of intrinsic carotenoids of LDL, and not, as is the case with some flavonoids, to the protection of intrinsic α-tocopherol (Grassmann et al, 2003(Grassmann et al, , 2005. Essential oils rich in phenolic constituents such as eugenol and thymol have the highest antioxidative activity against LDL oxidation (Naderi et al, 2004) and these components can also change the affinity of the LDL particles for the LDL receptor. A relationship was found between the quantity and quality of phenolic components in the oil and its protection against LDL oxidation: for instance, copper-catalysed oxidation of human LDL in vitro is inhibited by 50%-100% when eugenol is the major component of the essential oil (as in clove oil), while inhibition was only 10%-50% for essential oils containing moderate amounts of the phenolics, thymol, carvacrol or cuminol (Teissedre and Waterhouse, 2000).…”
Section: Essential Oils and Cardiovascular Diseases Atherosclerosismentioning
confidence: 99%
“…This inhibition is due to a retarded oxidation of intrinsic carotenoids of LDL, and not, as is the case with some flavonoids, to the protection of intrinsic α-tocopherol (Grassmann et al, 2003(Grassmann et al, , 2005. Essential oils rich in phenolic constituents such as eugenol and thymol have the highest antioxidative activity against LDL oxidation (Naderi et al, 2004) and these components can also change the affinity of the LDL particles for the LDL receptor. A relationship was found between the quantity and quality of phenolic components in the oil and its protection against LDL oxidation: for instance, copper-catalysed oxidation of human LDL in vitro is inhibited by 50%-100% when eugenol is the major component of the essential oil (as in clove oil), while inhibition was only 10%-50% for essential oils containing moderate amounts of the phenolics, thymol, carvacrol or cuminol (Teissedre and Waterhouse, 2000).…”
Section: Essential Oils and Cardiovascular Diseases Atherosclerosismentioning
confidence: 99%
“…The antioxidant activity of linalool has been wellestablished in previous studies ( 17,18 ). We reported that linalool could protect against hypercholesterolemia induced by high-fat diet through the downregulation of hepatic SREBP2-mediated cholesterol synthesis.…”
Section: Linalool Altered the Plasma Fa Metabolitementioning
confidence: 77%
“…Oral exposure to linalool from formulated food products, including beverages, was estimated at up to 140 g/kg/day, including the dietary intake of linalool from natural sources such as vegetables and spices ( 16 ). Linalool has been traditionally used for medicinal purposes because of its potent antioxidative activities ( 17,18 ). Recent studies have suggested that linalool may have a novel biological activity in TG metabolism, as the oral administration of fragrant herbal essential oils containing linalool, including Plantago asiatica and Melissa offi cinalis essential oils, was shown to improve dyslipidemia by reducing plasma TG concentrations ( 13,19 ).…”
Section: Nuclear Protein Preparation and Ppar ␣ Promoter Binding Assaymentioning
confidence: 99%
See 2 more Smart Citations